Skirmioni in topologija v magnetizmu - Podbregar, Lev (Matrika, 2024)
Skyrmions are unusual patterns of magnetic moments in crystals. They have the shape of small vortices of magnetization and are very stable due to their topological properties. In the article we will first look at their connection with topology, then we will get acquainted with the physical conditions necessary for their creation and conclude with the dynamics and possibilities of their application.
Keywords: crystals; feromagnetizem; ferromagnetism; kristali; skirmioni; skyrmions; topologija; topology